Heteroleptic Derivatives of Aluminium(III) as Precursors for Nano-Al2O3: A Study on the Influence of Ligands on Morphology of Alumina - Giri Prasanth, Vuppalapati; Venugopala Rao, Gojjala; Pathak, Madhvesh (Asian Journal of Chemistry, 2020)
Three metalloorganic derivatives of aluminium(III) [(CH3COCHCOOCH3)Al(OC6H4CH=NC6H4O)(EtOH)] (1), [(CH3COCHCOCH3)2Al(o-MeC6H4O)]2 (2) and Al(OiPr)3 (3) were exploited as precursors of alumina through well-established sol-gel hydrolytic pathway. The resultant white alumina powders (a), (b) and (c) were characterized by FTIR, powder XRD, TEM and EDX analyses. Formation of pure alumina was confirmed through EDX and FTIR techniques. The powder XRD patterns of alumina samples established their existence in γ-phase. The morphological examination of all oxidic ceramics through TEM illustrated that the alumina powders (a) and (b) were fine and discrete nanorods whereas alumina powder (c) was highly agglomerated with irregular morphology.